Formulation of 10% Glucose as a Mixture of Practicum Materials for Pregnancy Diabetes Mellitus Examination Skills in the Laboratory - Andi Zulfaidawaty; Marsuki Marsuki; Wirawati Amin (Jurnal Media Analis Kesehatan, 2023)
In laboratory-based learning, the use of formulated materials is crucial. A formulated glucose solution, with its predetermined composition, ready for use in observing Diabetes Mellitus (DM) scenarios in the laboratory, enables students to focus on direct experiences in simulating real-world situations. This enhances learning efficiency and provides greater opportunities for practical experiences. The objective of this research is to develop a formulation of a glucose 10% and aquadest mixture as synthetic urine to detect DM in laboratory skills activities. The experiment involved testing and observing a mixture of glucose 10% and aquadest. The resulting formula was tested using test strips and a heating procedure with Benedict's reagent. Five formulations, each prepared with a volume of 100 ml, yielded observations ranging from positive 1 to positive 4. Formula I, a mixture of 5 ml glucose 10% and 95 ml aquadest, resulted in a positive 4 observation. Formula II, with 4 ml glucose 10% and 96 ml aquadest, yielded a positive 3 observation. Formula III, with 3 ml glucose 10% and 97 ml aquadest, resulted in a positive 2 observation. Formula IV, with 2 ml glucose 10% and 98 ml aquadest, also produced a positive 2 observation. Formula V, a mixture of 1 ml glucose 10% and 99 ml aquadest, resulted in a positive 1 observation. It is recommended to prepare the mixture just before the activity, ensuring the cleanliness of containers to maintain the stability of the materials used. Further studies are needed to refine the formula with additional parameters